2007
DOI: 10.1051/0004-6361:20077655
|View full text |Cite
|
Sign up to set email alerts
|

SNLS spectroscopy: testing for evolution in type Ia supernovae

Abstract: Aims. We present a quantitative study of a new data set of high redshift Type Ia supernovae spectra, observed at the Gemini telescopes during the first 34 months of the Supernova Legacy Survey. During this time 123 supernovae candidates were observed, of which 87 have been identified as SNe Ia at a median redshift of z = 0.720. Spectra from the entire second year of the survey and part of the third year (59 total SNe candidates with 46 confirmed SNe Ia) are published here for the first time. The spectroscopic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(143 citation statements)
references
References 89 publications
11
130
2
Order By: Relevance
“…However, the presence of Si ii λ4000 in the Gemini spectrum contradicts this hypothesis, as this feature is not seen in under-luminous SNe because of extra absorption due to Ti ii and Fe ii in the same wavelength range. Based on this observation, Bronder et al (2008) concluded that 03D1co was likely to be a "normal" SN Ia, in agreement with its normal light curves (Astier et al 2006). The SALT2 fit of the VLT spectrum of 03D1co confirms this conclusion (see Fig.…”
Section: Peculiar Sn Iasupporting
confidence: 67%
See 4 more Smart Citations
“…However, the presence of Si ii λ4000 in the Gemini spectrum contradicts this hypothesis, as this feature is not seen in under-luminous SNe because of extra absorption due to Ti ii and Fe ii in the same wavelength range. Based on this observation, Bronder et al (2008) concluded that 03D1co was likely to be a "normal" SN Ia, in agreement with its normal light curves (Astier et al 2006). The SALT2 fit of the VLT spectrum of 03D1co confirms this conclusion (see Fig.…”
Section: Peculiar Sn Iasupporting
confidence: 67%
“…While the SN Ia category represents two thirds of our total sample, the number of SNe identified as "peculiar" is very small, which may reflect selection biases against such events (Bronder et al 2008). Low-stretch, underluminous SNe Ia are very hard to identify spectroscopically because of their dimness compared to their usually bright host.…”
Section: Sn Classificationmentioning
confidence: 99%
See 3 more Smart Citations